Reflection-type mask blank for EUV lithography, reflection-type mask for EUV lithography, and manufacturing methods therefor

JP2025029113AInactive Publication Date: 2025-03-05AGC INC

Patent Information

Application Number
JP2024210865
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-10-26
Filing Date
2024-12-04
Publication Date
2025-03-05
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0013】 本発明のEUVマスクブランクは、エッチングガスとして、ハロゲン系ガスを用いたドライエッチング、およびエッチングガスとして、酸素系ガスを用いたドライエッチングに対し、エッチング耐性に優れた保護膜を有する。 そのため、エッチングガスとして、ハロゲン系ガスを用いたドライエッチング、およびエッチングガスとして、酸素系ガスを用いたドライエッチングによる、多層反射膜のダメージが抑制される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029113000001
    Figure 2025029113000001
  • Figure 2025029113000002
    Figure 2025029113000002
  • Figure 2025029113000003
    Figure 2025029113000003
Patent Text Reader

Abstract

To provide an EUV mask blank which prevents damage to a multilayer reflective film due to dry etching using a halogen gas as an etching gas, and dry etching using an oxygen-based gas as an etching gas.SOLUTION: In a reflective mask blank for EUV lithography, a multilayer reflective film reflecting EUV light, a protective film for the multilayer reflective film, and an absorption layer absorbing EUV light are formed in this order. The protective film is made of rhodium (Rh) or a rhodium material including Rh and at least one element selected from the group consisting of nitrogen (N), oxygen (O), carbon (C), boron (B), ruthenium (Ru), niobium (Nb), molybdenum (Mo), tantalum (Ta), iridium (Ir), palladium (Pd), zirconium (Zr), and titanium (Ti).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a reflective mask blank for EUV (Extreme Ultra Violet) lithography (hereinafter referred to as "EUV mask blank" in this specification) used in semiconductor manufacturing or the like, a reflective mask for EUV lithography, and methods for manufacturing the same. [Background technology]

[0002] In the semiconductor industry, photolithography using visible light or ultraviolet light has been used as a transfer technique for fine patterns required to form integrated circuits consisting of fine patterns on Si substrates and the like. However, while the miniaturization of semiconductor devices is accelerating, the limit of conventional photolithography is approaching. In the case of photolithography, the resolution limit of the pattern is about 1 / 2 of the exposure wavelength. Even if the immersion method is used, it is said to be about 1 / 4 of the exposure wavelength, and even if the immersion method using ArF laser (193 nm) is used, the limit is expected to be about 20 nm to 30 nm. Therefore, EUV lithography, an exposure technology using EUV light with a shorter wavelength than ArF laser, is seen as promising as an exposure technology for 20 nm to 30 nm and below. In this specification, EUV light refers to light rays with a wavelength in the soft X-ray region or vacuum ultraviolet region. Specifically, it refers to light rays with a wavelength of about 10 nm to 20 nm, especially about 13.5 nm ± 0.3 nm.

[0003] EUV light is easily absorbed by all materials, and at this wavelength the refractive index of materials is close to 1. This means that refractive optics, as in conventional photolithography using visible or ultraviolet light, cannot be used, and so EUV lithography uses reflective optics, i.e., reflective masks and mirrors.

[0004] A mask blank is a pre-patterned laminate used for making photomasks. In the case of an EUV mask blank, a multilayer reflective film that reflects EUV light, a protective film, and an absorbing layer that absorbs EUV light are formed in this order on a substrate such as glass. The protective film protects the multilayer reflective film when a transfer pattern is formed in the absorbing layer by a dry etching process. Materials containing ruthenium (Ru) are widely used as materials for the protective film because they have a slower etching rate than the absorbing layer in dry etching using a halogen-based gas such as a chlorine-based gas as an etching gas, and are less susceptible to damage by this dry etching. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent No. 6343690 [Patent Document 2] Japanese Patent No. 3366572 Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, as patterns become finer and denser, higher resolution patterns are required. To obtain higher resolution patterns, it is necessary to reduce the thickness of the resist film. However, when the thickness of the resist is reduced, the resist film is consumed during the etching process, which may result in a decrease in the accuracy of the pattern transferred to the absorber layer. It is known that the resist can be made thinner by providing an etching mask film, which is resistant to the etching conditions of the absorbing layer, on the absorbing layer (see Patent Document 1).

[0007] In the EUV mask blank described in Patent Document 1, a material containing chromium (Cr) is used for the etching mask film. In the EUV mask blank described in Patent Document 1, dry etching is performed using a mixed gas of a chlorine-based gas and an oxygen gas as an etching gas, and the etching mask film using the material containing Cr is removed.

[0008] A protective film using a material containing Ru is etched by dry etching using a mixed gas of a chlorine-based gas and an oxygen gas as an etching gas (see Patent Document 2). Therefore, the protective film made of a material containing Ru may be damaged by dry etching using an oxygen-based gas, such as a mixed gas of a chlorine-based gas and an oxygen gas, as the etching gas.

[0009] In some cases, the absorber layer is made of a material containing Cr or ruthenium (Ru). In this case, a transfer pattern is formed on the absorber layer by dry etching using an oxygen-based gas as the etching gas. Therefore, the protective film made of a material containing Ru may be damaged.

[0010] If the protective film is damaged by the etching process, the multilayer reflective coating will also be damaged, which will lead to degradation of the optical properties of the EUV mask blank, such as a decrease in the reflectivity of the multilayer reflective coating.

[0011] In order to solve the above-mentioned problems of the conventional techniques, an object of the present invention is to provide an EUV mask blank which suppresses damage to a multilayer reflective film caused by dry etching using a halogen-based gas as an etching gas and dry etching using an oxygen-based gas as an etching gas. [Means for solving the problem]

[0012] [1] On the board, A multi-layer reflective film that reflects EUV light, a protective film for the multilayer reflective film; and a reflective mask blank for EUV lithography, comprising: A reflective mask blank for EUV lithography, characterized in that the protective film is made of rhodium (Rh) or a rhodium-based material containing Rh and at least one element selected from the group consisting of nitrogen (N), oxygen (O), carbon (C), boron (B), ruthenium (Ru), niobium (Nb), molybdenum (Mo), tantalum (Ta), iridium (Ir), palladium (Pd), zirconium (Zr) and titanium (Ti). [2] The reflective mask blank for EUV lithography according to [1], wherein the protective film contains Rh and at least one element selected from the group consisting of N, O, C and B. [3] The reflective mask blank for EUV lithography according to [2], wherein the protective film contains Rh in an amount of 40 at % or more and 99 at % or less, and at least one element selected from the group consisting of N, O, C, and B in an amount of 1 at % or more and 60 at % or less. [4] The protective film contains 90 at % or more Rh and has a film density of 10.0 to 14.0 g cm -3 The reflective mask blank for EUV lithography according to [1], [5] The reflective mask blank for EUV lithography according to any one of [1] to [4], wherein the protective film contains at least one element (X) selected from the group consisting of Ru, Nb, Mo, Ta, Ir, Pd, Zr, and Ti in a composition ratio (at%) of Rh to X (Ru:X) in the range of 99:1 to 1:1. [6] The reflective mask blank for EUV lithography according to any one of [1] to [5], wherein the protective film has a thickness of 1.0 nm or more and 10.0 nm or less. [7] The reflective mask blank for EUV lithography according to any one of [1] to [6], wherein the protective film has a surface roughness (rms) of 0.3 nm or less. [8] The reflective mask blank for EUV lithography according to any one of [1] to [7], further comprising a diffusion barrier layer between the multilayer reflective film and the protective film, the diffusion barrier layer containing at least one element selected from Nb, Ru, Ta, silicon (Si), Zr, Ti and Mo. [9] The reflective mask blank for EUV lithography according to [8], wherein the diffusion barrier layer further contains at least one element selected from the group consisting of O, N, C and B.

[10] The reflective mask blank for EUV lithography according to any one of [1] to [9], wherein the absorption layer contains at least one element selected from Ru, Ta, chromium (Cr), Nb, platinum (Pt), Ir, rhenium (Re), tungsten (W), manganese (Mn), gold (Au), Si, aluminum (Al) and hafnium (Hf).

[11] The reflective mask blank for EUV lithography according to

[10] , wherein the absorber layer further contains at least one element selected from the group consisting of O, N, C and B.

[12] The reflective mask blank for EUV lithography according to any one of [1] to

[11] , further comprising an etching mask film on the absorption layer, the etching mask film containing at least one element selected from the group consisting of Cr, Nb, Ti, Mo, Ta and Si.

[13] The reflective mask blank for EUV lithography according to

[12] , wherein the etching mask film further contains at least one element selected from the group consisting of O, N, C and B.

[14] A reflective mask for EUV lithography, comprising the reflective mask blank for EUV lithography according to any one of [1] to

[13] , wherein a pattern is formed in the absorption layer.

[15] forming a multilayer reflective film on a substrate that reflects EUV light; forming a protective film on the multilayer reflective film; forming an absorption layer that absorbs EUV light on the protective film; a rhodium-based material containing Rh or Rh and at least one element selected from the group consisting of N, O, C, B, Ru, Nb, Mo, Ta, Ir, Pd, Zr and Ti;

[16] A method for manufacturing a reflective mask for EUV lithography, comprising patterning an absorbing layer in a reflective mask blank for EUV lithography manufactured by the method for manufacturing a reflective mask blank for EUV lithography described in

[15] to form a pattern. Effect of the Invention

[0013] The EUV mask blank of the present invention has a protective film that has excellent etching resistance to dry etching using a halogen-based gas as an etching gas and to dry etching using an oxygen-based gas as an etching gas. Therefore, damage to the multilayer reflective film caused by dry etching using a halogen-based gas as an etching gas and dry etching using an oxygen-based gas as an etching gas is suppressed. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of an EUV mask blank of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another embodiment of the EUV mask blank of the present invention. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing still another embodiment of the EUV mask blank of the present invention. [Figure 4] FIG. 4 is a schematic cross-sectional view showing one embodiment of the EUV mask of the present invention. [Diagram 5] FIG. 5 is a diagram showing the results of TEM observation of a sample of Example 1 after dry etching treatment with an oxygen-based gas. [Figure 6] FIG. 6 is a diagram showing the results of TEM observation of a sample in Example 6 after dry etching treatment with an oxygen-based gas. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The EUV mask blank of the present invention will now be described with reference to the drawings. Fig. 1 is a schematic cross-sectional view showing one embodiment of an EUV mask blank of the present invention. In the EUV mask blank 1a shown in Fig. 1, a multilayer reflective film 12 that reflects EUV light, a protective film 13 for the multilayer reflective film 12, and an absorption layer 14 that absorbs EUV light are formed in this order on a substrate 11.

[0016] Hereinafter, the individual components of the EUV mask blank 1a will be described.

[0017] The substrate 11 satisfies the characteristics required for an EUV mask blank substrate. To this end, the substrate 11 has a low thermal expansion coefficient (specifically, a thermal expansion coefficient of 0±0.05×10 at 20° C.). -7 / °C is preferable, and 0±0.03×10 -7 / °C), and has excellent smoothness, flatness, and resistance to cleaning solutions using acids or bases. Specifically, glass having a low thermal expansion coefficient, such as SiO2-TiO2 glass, is used as the substrate 11, but is not limited thereto, and substrates such as crystallized glass in which a β-quartz solid solution is precipitated, quartz glass, silicon, and metal can also be used. It is preferable that the substrate 11 has a smooth surface with a surface roughness (rms) of 0.15 nm or less and a flatness of 100 nm or less, because this allows high reflectance and transfer accuracy to be obtained in the reflective mask after pattern formation. The size and thickness of the substrate 11 are appropriately determined based on the design values ​​of the mask, etc. In the embodiment shown later, SiO2-TiO2 glass having an outer shape of 6 inches (152 mm) square and a thickness of 0.25 inches (6.3 mm) was used. It is preferable that there are no defects on the surface of the substrate 11 on which the multilayer reflective film 12 is formed. However, even if defects are present, it is acceptable as long as no phase defects are caused by concave defects and / or convex defects. Specifically, it is preferable that the depth of the concave defect and the height of the convex defect are 2 nm or less, and that the half-width of these concave defects and convex defects are 60 nm or less. The half-width of a concave defect refers to the width at a position half the depth of the concave defect. The half-width of a convex defect refers to the width at a position half the height of the convex defect.

[0018] The multilayer reflective film 12 achieves high EUV light reflectance by alternately stacking high refractive index layers and low refractive index layers multiple times. In the multilayer reflective film 12, Mo is widely used for the high refractive index layers, and Si is widely used for the low refractive index layers. That is, a Mo / Si multilayer reflective film is the most common. However, the multilayer reflective film is not limited to this, and Ru / Si multilayer reflective film, Mo / Be multilayer reflective film, Mo compound / Si compound multilayer reflective film, Si / Mo / Ru multilayer reflective film, Si / Mo / Ru / Mo multilayer reflective film, and Si / Ru / Mo / Ru multilayer reflective film can also be used.

[0019] The multilayer reflective film 12 is not particularly limited as long as it has the desired properties as a multilayer reflective film for a reflective mask blank. Here, the property particularly required for the multilayer reflective film 12 is high EUV light reflectance. Specifically, when a light beam in the wavelength region of EUV light is irradiated onto the surface of the multilayer reflective film 12 at an incident angle of 6 degrees, the maximum value of the light reflectance at a wavelength of about 13.5 nm is preferably 60% or more, more preferably 65% ​​or more.

[0020] The thickness of each layer constituting the multilayer reflective film 12 and the number of repeat units of the layers can be appropriately selected depending on the film material used and the EUV light reflectance required for the multilayer reflective film. Taking a Mo / Si multilayer reflective film as an example, in order to obtain a multilayer reflective film 12 with a maximum EUV light reflectance of 60% or more, the multilayer reflective film may be formed by laminating Mo layers with a thickness of 2.3±0.1 nm and Si layers with a thickness of 4.5±0.1 nm so that the number of repeat units is 30 or more and 60 or less.

[0021] Each layer constituting the multilayer reflective film 12 may be formed to a desired thickness using a known film formation method such as magnetron sputtering or ion beam sputtering. For example, when forming a Si / Mo multilayer reflective film using ion beam sputtering, a Si target is used as the target, and Ar gas (gas pressure 1.3×10) is used as the sputtering gas. -2 Pa or more 2.7×10 -2A Si layer was formed to a thickness of 4.5 nm using an ion accelerating voltage of 300 V to 1500 V and a deposition rate of 0.030 nm / sec to 0.300 nm / sec, and then a Mo target was used as the sputtering gas, and Ar gas (gas pressure 1.3 × 10 -2 Pa or more 2.7×10 -2 It is preferable to deposit the Mo layer to a thickness of 2.3 nm using a vacuum pump (pressure equal to or less than 1 Pa) at an ion acceleration voltage of 300 V to 1500 V and a deposition rate of 0.030 nm / sec to 0.300 nm / sec. This is counted as one cycle, and the Si / Mo multilayer reflective film is deposited by laminating the Si layer and the Mo layer for 40 to 50 cycles.

[0022] In order to prevent oxidation of the surface of the multilayer reflective film 12, the top layer of the multilayer reflective film 12 is preferably a layer of a material that is resistant to oxidation. The layer of the material that is resistant to oxidation functions as a capping layer for the multilayer reflective film 12. A specific example of a layer of a material that is resistant to oxidation that functions as a capping layer is a Si layer. When the multilayer reflective film 12 is a Si / Mo film, if the top layer is a Si layer, the top layer functions as a capping layer. In this case, the thickness of the capping layer is preferably 11±2 nm.

[0023] The protective film 13 in the present invention is made of rhodium (Rh) or a rhodium-based material containing Rh and at least one element selected from the group consisting of nitrogen (N), oxygen (O), carbon (C), boron (B), ruthenium (Ru), niobium (Nb), molybdenum (Mo), tantalum (Ta), iridium (Ir), palladium (Pd), zirconium (Zr) and titanium (Ti). The protective film made of Rh or a rhodium-based material has a low etching rate when dry etching using a halogen-based gas as an etching gas (hereinafter, may be referred to as "dry etching with a halogen-based gas") and dry etching using an oxygen-based gas as an etching gas (hereinafter, may be referred to as "dry etching with an oxygen-based gas") are performed. Therefore, the film exhibits excellent resistance to both dry etching with a halogen-based gas, which is widely used when forming a pattern on the absorption layer 14, and dry etching with an oxygen-based gas, which is used when removing an etching mask film or when forming a pattern on the absorption layer 14 using a ruthenium (Ru)-based material, which will be described later. Dry etching with halogen-based gases refers to dry etching using chlorine-based gases such as Cl2, SiCl4, CHCl3, CCl4, BCl3, etc., and mixed gases of these, as well as dry etching using fluorine-based gases such as CF4, CHF3, SF6, BF3, XeF2, etc., and mixed gases of these. Dry etching with oxygen-based gas refers to dry etching using oxygen gas and dry etching using a mixed gas of oxygen gas and a halogen-based gas. As the halogen-based gas, the above-mentioned chlorine-based gas and mixed gas thereof, and the above-mentioned fluorine-based gas and mixed gas thereof are used.

[0024] The resistance of the protective film 13 to dry etching with a halogen-based gas and the resistance of the protective film 13 to dry etching with an oxygen-based gas can be evaluated by the etching selectivity to the absorbing layer 14 calculated by the following formula. Etching Selectivity = Etching rate of protective film 13 / Etching rate of absorbing layer 14 The protective film 13 preferably has an etching selectivity of 1 / 5 or less with respect to the absorbing layer 14 in both dry etching with a halogen-based gas and dry etching with an oxygen-based gas.

[0025] The protective film 13 is required to be resistant to sulfuric acid / hydrogen peroxide (SPM), which is used as a cleaning liquid for resist in EUV lithography. A protective film made of Rh or a rhodium-based material has excellent resistance to SPM.

[0026] The EUV mask blank is required to achieve high EUV light reflectance even in a state where the protective film 13 is provided on the multilayer reflective film 12. Specifically, even in a state where the protective film 13 is provided on the multilayer reflective film 12, the maximum light reflectance at a wavelength of about 13.5 nm is preferably 60% or more, and more preferably 65% ​​or more. A protective film made of Rh or a rhodium-based material has a low refractive index and extinction coefficient in the wavelength range of EUV light. Therefore, the above-mentioned EUV light reflectance can be achieved.

[0027] The protective film 13 made of Rh has particularly excellent resistance to dry etching with a halogen-based gas and dry etching with an oxygen-based gas.

[0028] The protective film 13 made of a rhodium-based material containing Rh and at least one element (X) selected from the group consisting of Ru, Nb, Mo, Ta, Ir, Pd, Zr, and Ti is an alloy film of Rh and the element X. The alloy film of Rh and the element X has lower resistance to dry etching with a halogen-based gas and dry etching with an oxygen-based gas compared to a protective film made of Rh, but improves the EUV light reflectance when the protective film 13 is provided on the multilayer reflective film 12. As the element X, Ru, Nb, Mo, and Zr are preferable because they improve the EUV light reflectance when the protective film 13 is provided on the multilayer reflective film 12. The alloy film of Rh and element X preferably contains Rh and element X in a composition ratio (at%) of Rh to X (Ru:X) in the range of 99:1 to 1:1. When the composition ratio (at%) of Rh to X is greater than 99:1, the EUV light reflectance is improved in a state where the protective film 13 is provided on the multilayer reflective film 12. When the composition ratio (at%) of Rh to X is less than 1:1, the resistance to dry etching with a halogen-based gas and dry etching with an oxygen-based gas is excellent. The alloy film of Rh and element X preferably contains Rh and element X in a composition ratio (at%) of Rh to X (Ru:X) in the range of 10:3 to 1:1.

[0029] When dry etching using a mixed gas of oxygen gas and halogen gas is performed as dry etching using oxygen-based gas, the etching speed of the protective film made of Rh or Rh-based material does not change significantly even if the mixture ratio of oxygen gas and halogen gas is changed. Therefore, by adjusting the mixture ratio of oxygen gas and halogen gas so that the etching speed of the absorbing layer 14 is maximized, the etching selectivity for the absorbing layer 14 can be reduced.

[0030] The protective film 13 in the present invention may contain at least one element Y selected from the group consisting of N, O, C and B in addition to Rh or Rh and element X. When the protective film 13 contains element Y, the resistance to dry etching with a halogen-based gas and dry etching with an oxygen-based gas decreases, but the crystallinity of the film decreases, and the crystalline state of the film becomes an amorphous structure or a microcrystalline structure. This improves the smoothness of the protective film. Whether the crystalline state of the film is an amorphous structure or a microcrystalline structure can be confirmed by X-ray diffraction (XRD). If the crystalline state of the film is an amorphous structure or a microcrystalline structure, no sharp peak is observed in the diffraction peak obtained by XRD measurement. When the element Y contains at least one element selected from the group selected from N, O, C, and B, it is preferable that the total of Rh or Rh and the element X is 40 at% or more and 99 at% or less, and that the total of at least one element selected from the group selected from N, O, C, and B is 1 at% or more and 60 at% or less, and it is more preferable that the total of Rh or Rh and the element X is 80 at% or more and 99 at% or less, and that the total of at least one element selected from the group selected from N, O, C, and B is 1 at% or more and 20 at% or less.

[0031] The protective film 13 contains 90 at % or more of Rh and has a film density of 10.0 to 14.0 g cm -3 In this case, the crystallinity of the film is also low, and the crystalline state of the film becomes an amorphous structure or a microcrystalline structure. This improves the smoothness of the protective film. In this case, the protective film 13 contains element X and / or element Y in addition to Rh. The film density of the protective film 13 is 11.0 to 13.0 g cm -3 Even when the protective film 13 contains Rh at 100 at %, that is, when the protective film 13 is made of Rh, the film density is preferably 11.0 to 12.0 g cm -3 Within this range, the crystallinity of the film is low, and the crystalline state of the film is an amorphous structure or a microcrystalline structure, thereby improving the smoothness. In the examples described below, the film density of the protective film 13 was measured using X-ray reflectivity, but this is not limited to this. For example, the density can also be calculated as the ratio of the surface density measured by Rutherford backscattering spectroscopy to the film thickness measured by a transmission electron microscope.

[0032] The thickness of the protective film 13 is preferably 1.0 nm or more and 10.0 nm or less, and more preferably 2.0 nm or more and 3.5 nm or less.

[0033] The protective film 13 preferably has excellent surface smoothness. When the protective film 13 has excellent surface smoothness, the surface smoothness of the absorption layer 14 formed on the protective film 13 is improved. The surface roughness (rms) of the protective film surface is preferably 0.3 nm or less, and more preferably 0.1 nm or less. The surface roughness (rms) of the protective film surface is preferably 0.001 nm or more, and more preferably 0.01 nm or more.

[0034] The protective film 13 is formed by a known film formation method such as magnetron sputtering or ion beam sputtering. For example, when a Rh film is formed by DC sputtering, a Rh target is used as the target, and Ar gas (gas pressure 1.0×10 -2 Pa or more 1.0×10 0 Pa or less) with a power density of 1.0 W / cm per target area. 2 More than 8.5W / cm 2 It is preferable to form the film at a film formation speed of 0.020 nm / sec to 1.000 nm / sec and to a thickness of 1 nm to 10 nm. When forming an Rh film, the sputtering gas is N2 gas or a mixed gas of Ar gas and N2 (the volume ratio of N2 gas in the mixed gas (N2 / (Ar+N2)) = 0.05 to 1.0), and the gas pressure is 1.0 × 10 -2 Pa or more 1.0×10 0 Pa or less) may be used. When forming an RhO film using the DC sputtering method, an Rh target is used as the target, and O2 gas or a mixed gas of Ar gas and O2 (volume ratio of O2 gas in the mixed gas (O2 / (Ar+O2)) = 0.05 to 1.0) is used as the sputtering gas, with a gas pressure of 1.0 x 10 -2 Pa or more 1.0×10 0 Pa or less) with a power density of 1.0 W / cm per target area. 2 More than 8.5W / cm 2It is preferable to form the film at a film formation rate of 0.020 nm / sec to 1.000 nm / sec and to a thickness of 1 nm to 10 nm. When forming the RhRu film by DC sputtering, a Rh target and a Ru target, or a RhRu target, are used as targets, and Ar gas (gas pressure 1.0×10 -2 Pa or more 1.0×10 0 Pa or less) with a power density of 1.0 W / cm per target area. 2 More than 8.5W / cm 2 Hereinafter, it is preferable to form the film at a film formation rate of 0.020 nm / sec to 1.000 nm / sec to a thickness of 1 nm to 10 nm.

[0035] The absorbing layer 14 preferably includes at least one element selected from Ru, Ta, chromium (Cr), Nb, platinum (Pt), Ir, rhenium (Re), tungsten (W), manganese (Mn), gold (Au), Si, aluminum (Al) and hafnium (Hf).

[0036] In the case of the absorbing layer 14 for a binary mask, the absorbing layer 14 preferably contains at least one element selected from Ta, Nb, Pt, Ir, Re and Cr, more preferably contains at least one element selected from Ta and Nb, and further preferably contains Ta. When the absorbing layer 14 contains at least one of Ta and Nb, it is preferable to form a transfer pattern by dry etching with a halogen-based gas, and it is more preferable to perform dry etching using a chlorine-based gas as the dry etching with the halogen-based gas. When the absorbing layer 14 contains at least one of Pt and Ir, it is preferable to form a transfer pattern by dry etching with a halogen-based gas, and it is preferable to use a fluorine-based gas as the halogen-based gas. When the absorbing layer 14 contains at least one of Cr and Re, it is preferable to form a transfer pattern by dry etching with an oxygen-based gas, and it is more preferable to perform dry etching using a mixed gas of oxygen gas and chlorine gas as the dry etching with the oxygen-based gas.

[0037] In the case of the absorption layer 14 for a phase shift mask, the absorption layer 14 preferably contains Ru, and more preferably further contains at least one element selected from Ta, Cr, Ir, Re, W, and Hf. When Ru and the above element are contained, Ru and the above element form an alloy. In the case of a Ru alloy containing Ru and at least one element selected from Ta, Cr, Ir, Re, W, and Hf, the EUV light reflectance can be controlled by the content of the above element relative to Ru, so that the content of the above element can be adjusted to obtain a desired EUV light reflectance. On the other hand, if the content of the above element relative to Ru is too high, the refractive index n in the wavelength range of EUV light becomes large, and the film thickness required to invert the phase becomes large, so the content of the above element is preferably 50 at% or less relative to Ru. Note that, when the Ru alloy contains two or more of the above elements, the content of the above element refers to the total content of the two or more elements. When the absorption layer 14 contains Ru or a Ru alloy containing Ru and at least one element selected from Ta, Cr, Ir, Re, W and Hf, it is preferable to form a transfer pattern by dry etching with an oxygen-based gas, and more preferably, dry etching is performed using a mixed gas of oxygen gas and a halogen-based gas as the dry etching with an oxygen-based gas. The etching rate of the absorption layer 14 can be adjusted by the mixture ratio of oxygen gas and halogen-based gas in the oxygen-based gas. The mixture ratio of oxygen gas and halogen-based gas is preferably 10:90 to 50:50 in terms of the volume ratio of oxygen gas to halogen-based gas (oxygen gas: halogen-based gas), and more preferably 20:80 to 40:60. In addition, when the Ru alloy contains at least one element selected from Ta, Cr, Ir and W, it is preferable to use a fluorine-based gas as the halogen-based gas.

[0038] In both the case of the absorption layer 14 for a binary mask and the absorption layer 14 for a phase shift mask, the absorption layer 14 may contain at least one element selected from the group consisting of O, N, C, and B in addition to the above elements. By containing these elements, the crystallinity of the film is reduced and the surface smoothness of the absorption layer is improved. It is more preferable to contain at least one element selected from the group consisting of O, N, and B, and further more preferable to contain at least one element selected from the group consisting of O and N. The absorption layer 14 for a binary mask may be, for example, a TaN film containing Ta and N. The absorption layer 14 for a phase shift mask may be, for example, a RuON film containing Ru, O and N.

[0039] In both cases of the absorbing layer 14 for a binary mask and the absorbing layer 14 for a phase shift mask, the thickness of the absorbing layer 14 is preferably 20 nm to 80 nm, more preferably 30 nm to 70 nm, and further preferably 40 nm to 60 nm.

[0040] In both cases of the absorbing layer 14 for a binary mask and the absorbing layer 14 for a phase shift mask, the layer is formed by a known film formation method such as magnetron sputtering or ion beam sputtering. For example, when forming a TaN film by magnetron sputtering, a Ta target is used as the target, and a mixed gas of Ar and N2 (gas pressure 1.0×10 -1 Pa or more 50×10 -1 Pa or less) with an input power density of 1.0 W / cm 2 More than 8.5W / cm 2 Hereinafter, it is preferable to form the film at a film formation rate of 0.020 nm / sec to 1.000 nm / sec to a thickness of 20 nm to 80 nm. When forming a RuON film by magnetron sputtering, a Ru target is used as the target, and a mixed gas containing Ar, O2, and N2 (gas pressure 1.0×10 -2 Pa or more 1.0×10 0Pa or less) with an input power density of 1.0 W / cm 2 More than 8.5W / cm 2 Hereinafter, it is preferable to form the film at a film formation rate of 0.020 nm / sec to 1.000 nm / sec to a thickness of 20 nm to 80 nm. When forming a RuN film by magnetron sputtering, a Ru target is used as the target, and a mixed gas of Ar and N2 (gas pressure 1.0×10 -2 Pa or more 1.0×10 0 Pa or less) with an input power density of 1.0 W / cm 2 More than 8.5W / cm 2 Hereinafter, it is preferable to form the film at a film formation rate of 0.020 nm / sec to 1.000 nm / sec to a thickness of 20 nm to 80 nm. When forming a RuB film by magnetron sputtering, a Ru target and a B target, or a RuB compound target, are used as targets, and Ar gas (gas pressure 1.0×10 -2 Pa or more 1.0×10 0 Pa or less) using an input power density of 0.1 W / cm 2 More than 8.5W / cm 2 Hereinafter, it is preferable to form the film at a film formation rate of 0.010 nm / sec to 1.000 nm / sec to a thickness of 20 nm to 80 nm. When forming a RuTa film by magnetron sputtering, a Ru target and a Ta target, or a RuTa compound target, are used as targets, and Ar gas (gas pressure 1.0×10 -2 Pa or more 1.0×10 0 Pa or less) using an input power density of 0.1 W / cm 2 More than 8.5W / cm 2 Hereinafter, it is preferable to form the film at a film formation rate of 0.020 nm / sec to 1.000 nm / sec to a thickness of 20 nm to 80 nm. When forming a RuW film by magnetron sputtering, a Ru target and a W target, or a RuW compound target, are used as targets, and Ar gas (gas pressure 1.0×10 -2 Pa or more 1.0×10 0 Pa or less) using an input power density of 0.1 W / cm 2 More than 8.5W / cm 2 Hereinafter, it is preferable to form the film at a film formation rate of 0.020 nm / sec to 1.000 nm / sec to a thickness of 20 nm to 80 nm. When forming a RuCr film by magnetron sputtering, a Ru target and a Cr target, or a RuCr compound target, are used as targets, and Ar gas (gas pressure 1.0×10 -2 Pa or more 1.0×10 0 Pa or less) using an input power density of 0.1 W / cm 2 More than 8.5W / cm 2 Hereinafter, it is preferable to form the film at a film formation rate of 0.020 nm / sec to 1.000 nm / sec to a thickness of 20 nm to 80 nm.

[0041] The absorbing layer containing Ta, which is suitable as the absorbing layer 14 for a binary mask, can form a transfer pattern by dry etching with a halogen-based gas. The Ru-containing absorbing layer, which is suitable as the absorbing layer 14 for a phase shift mask, can form a transfer pattern by dry etching with an oxygen-based gas.

[0042] Fig. 2 is a schematic cross-sectional view showing another embodiment of the EUV mask blank of the present invention. The EUV mask blank 1b shown in Fig. 2 has a multilayer reflective film 12, a diffusion barrier layer 15, a protective film 13, and an absorbing layer 14 formed in this order on a substrate 11. Of the components of the EUV mask blank 1b, the substrate 11, the multilayer reflective film 12, the protective film 13, and the absorbing layer 14 are the same as those of the above-mentioned EUV mask blank 1a, and therefore will not be described.

[0043] There is a risk of a decrease in EUV reflectance if the Rh or rhodium-based material of the protective film 13 diffuses into the top layer (Si layer) of the multilayer reflective film 12. By providing the diffusion barrier layer 15, it is possible to suppress the diffusion of the Rh or rhodium-based material of the protective film 13 into the top layer (Si layer) of the multilayer reflective film 12. The diffusion barrier layer 15 preferably contains at least one element selected from Nb, Ru, Ta, Si, Zr, Ti and Mo, and more preferably contains at least one element selected from Nb, Si and Ru.

[0044] In addition to the above elements, the diffusion barrier layer 15 may contain at least one element selected from the group consisting of O, N, C, and B. By containing these elements, the thickness of the diffusion barrier layer 15 required for suppressing diffusion from the protective film 13 to the multilayer reflective film 12 can be reduced. It is more preferable that the diffusion barrier layer 15 contains at least one element selected from the group consisting of O, N, and B, and it is even more preferable that the diffusion barrier layer 15 contains at least one element selected from the group consisting of O and N.

[0045] The thickness of the diffusion barrier layer 15 is preferably 0.5 nm or more and 2.0 nm or less, and more preferably 0.5 nm or more and 1.0 nm or less.

[0046] The diffusion barrier layer 15 is formed by a known film formation method such as magnetron sputtering or ion beam sputtering. When forming a Ru film by magnetron sputtering, a Ru target is used as the target, and Ar gas (gas pressure 1.0×10 -2 Pa or more 1.0×10 0 It is preferable to use a voltage of 30 V to 1500 V, a deposition rate of 0.020 nm / sec to 1.000 nm / sec, and a thickness of 0.1 nm to 2 nm.

[0047] Fig. 3 is a schematic cross-sectional view showing yet another embodiment of an EUV mask blank of the present invention. In the EUV mask blank 1c shown in Fig. 3, a multilayer reflective film 12, a protective film 13, an absorbing layer 14, and an etching mask film 16 are formed in this order on a substrate 11. Of the components of the EUV mask blank 1c, the substrate 11, the multilayer reflective film 12, the protective film 13, and the absorbing layer 14 are the same as those of the above-mentioned EUV mask blank 1a, and therefore will not be described.

[0048] In the EUV mask blank 1c shown in FIG. 3, an etching mask film 16 is provided on the absorbing layer 14, thereby making it possible to reduce the thickness of the resist. The etching mask film 16 preferably contains at least one element selected from the group consisting of Cr, Nb, Ti, Mo, Ta and Si. In the case of an absorber layer containing Ta, which is suitable as the absorber layer 14 for a binary mask, the etching mask film 16 preferably contains Cr. In the case of an absorbing layer containing Ru, which is suitable as the absorbing layer 14 for a phase shift mask, the etching mask film 16 preferably contains Nb.

[0049] In addition to the above elements, the etching mask film 16 may contain at least one element selected from the group consisting of O, N, C, and B. It is more preferable that the etching mask film 16 contains at least one element selected from the group consisting of O, N, and B, and it is even more preferable that the etching mask film 16 contains at least one element selected from the group consisting of O and N.

[0050] The thickness of the etching mask film 16 is preferably 2 nm or more and 30 nm or less, more preferably 2 nm or more and 25 nm or less, and further preferably 2 nm or more and 10 nm or less.

[0051] The etching mask film 16 can be formed by a known film forming method, for example, magnetron sputtering or ion beam sputtering.

[0052] The EUV mask blanks 1a to 1c of the present invention may have a functional film known in the field of EUV mask blanks, in addition to the multilayer reflective film 12, the protective film 13, the diffusion barrier layer 15, the absorbing layer 14, and the etching mask film 16. A specific example of such a functional film is a high dielectric coating applied to the back side of the substrate to promote electrostatic chucking of the substrate, as described in JP 2003-501823 A. Here, the back side of the substrate refers to the surface of the substrate 11 in FIG. 1 opposite to the side on which the multilayer reflective film 12 is formed. The high dielectric coating applied to the back side of the substrate for such a purpose is selected so that the electrical conductivity and thickness of the constituent material are such that the sheet resistance is 100Ω / □ or less. The constituent material of the high dielectric coating can be widely selected from those described in known documents. For example, a high dielectric constant coating described in JP 2003-501823 A, specifically, a coating made of silicon, TiN, molybdenum, chromium, and TaSi can be applied. The thickness of the high dielectric coating can be, for example, 10 nm to 1000 nm. The high dielectric coating can be formed by using a known film formation method, for example, a sputtering method such as magnetron sputtering or ion beam sputtering, a CVD method, a vacuum deposition method, or an electrolytic plating method.

[0053] The method for producing an EUV mask blank of the present invention includes the following steps a) to c). a) A process for forming a multilayer reflective film that reflects EUV light on a substrate b) forming a protective film made of Rh or a rhodium-based material on the multilayer reflective film formed in step a) c) forming an absorption layer that absorbs EUV light on the protective film formed in step b) According to the method for producing an EUV mask blank of the present invention, an EUV mask blank 1a shown in FIG. 1 is obtained.

[0054] Fig. 4 is a schematic cross-sectional view showing one embodiment of the EUV mask of the present invention. In the EUV mask 2 shown in Fig. 4, a pattern (absorption layer pattern) 140 is formed in the absorption layer 14 of the EUV mask blank 1a shown in Fig. 1. That is, a multilayer reflective film 12 that reflects EUV light, a protective film 13 for the multilayer reflective film 12, and an absorption layer 14 that absorbs EUV light are formed in this order on a substrate 11, and a pattern (absorption layer pattern) 140 is formed in the absorption layer 14. Of the components of the EUV mask 2, the substrate 11, the multilayer reflective film 12, the protective film 13, and the absorbing layer 14 are the same as those of the above-described EUV mask blank 1a. In the EUV mask manufacturing method of the present invention, a pattern is formed by patterning the absorbing layer 14 of the EUV mask blank manufactured by the EUV mask blank manufacturing method of the present invention. Since the protective film 13 of the EUV mask blank of the present invention has excellent resistance to dry etching with a halogen-based gas and dry etching with an oxygen-based gas, damage to the multilayer reflective film 12 during patterning of the absorbing layer 14 can be suppressed. EXAMPLES

[0055] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples. Among Examples 1 to 19, Examples 1 to 5 and Examples 8 to 19 are working examples, and Examples 6 and 7 are comparative examples.

[0056] <Example 1> In Example 1, an EUV mask blank shown in FIG. 1 was produced. A SiO2-TiO2 glass substrate (6-inch (152 mm) square, 6.3 mm thick) was used as the substrate for film formation. The thermal expansion coefficient of this glass substrate at 20°C is 0.02×10 -7 / ℃, Young's modulus is 67GPa, Poisson's ratio is 0.17, and specific rigidity is 3.07×10 7 m 2 / s 2 The glass substrate was polished to a smooth surface with a surface roughness (rms) of 0.15 nm or less and a flatness of 100 nm or less.

[0057] On the back side of the substrate, a high-dielectric coating with a sheet resistance of 100 Ω / sq was applied by forming a Cr film with a thickness of 100 nm using the magnetron sputtering method. A substrate (outer shape: 6 inches (152 mm) square, thickness: 6.3 mm) was fixed to a normal electrostatic chuck having a flat plate shape via the formed Cr film, and the formation of an Si film and a Mo film alternately on the surface of the substrate using the ion beam sputtering method was repeated 40 cycles, thereby forming an Si / Mo multilayer reflective film 12 with a total film thickness of 272 nm ((4.5 nm + 2.3 nm) × 40). Furthermore, a protective film was formed by forming a Rh film (film thickness: 2.5 nm) on the Si / Mo multilayer reflective film using the DC sputtering method. The EUV light reflectivity after forming the protective film was 64.5% at maximum.

[0058] The film formation conditions for the Si film, Mo film, and Rh film are as follows. <Film formation conditions for Si film> Target: Si target (boron-doped) Sputtering gas: Ar gas (gas pressure: 2.0×10 -2 Pa) Voltage: 700 V Film formation rate: 0.077 nm / sec Film thickness: 4.5 nm <Film formation conditions for Mo film> Target: Mo target Sputtering gas: Ar gas (gas pressure: 2.0×10 -2 Pa) Voltage: 700 V Film formation rate: 0.064 nm / sec Film thickness: 2.3 nm <Film formation conditions for Rh film> Target: Rh target Sputtering gas: Ar gas (gas pressure: 2.0×10 -2 Pa) Input power density per target area: 3.7 W / cm 2 Film formation rate: 0.048 nm / sec

[0059] Next, an absorption layer containing RuON (RuON film), an absorption layer containing RuN (RuN film), or an absorption layer containing TaN (TaN film) was formed on the protective film using a reactive sputtering method as a magnetron sputtering method. The film formation conditions for the absorption layer containing RuON (RuON film), the absorption film containing RuN (RuN film), and the absorption layer containing TaN (TaN film) are as follows. <Film formation conditions for RuON film> Target: Ru target Sputtering gas: Mixed gas of Ar gas, O2, and N2 (volume ratio of O2 gas in the mixed gas (O2 / (Ar + O2 + N2)) = 0.17, volume ratio of N2 gas in the mixed gas (N2 / (Ar + O2 + N2)) = 0.17, gas pressure: 2.0×10 -1 Pa) Input power density per target area: 7.4 W / cm 2 Film formation rate: 0.20 nm / sec The composition ratio (at%) of RuON is Ru:O:N = 40:55:5. Film thickness: 52 nm <Film formation conditions for RuN film> Target: Ru target Sputtering gas: Mixed gas of Ar gas and N2 (volume ratio of N2 gas in the mixed gas (N2 / (Ar + N2)) = 0.17, gas pressure: 2.0×10 -1 Pa) Input power density per target area: 6.2 W / cm 2 Film formation rate: 0.20 nm / sec The composition ratio (at%) of RuN is Ru:N = 98:2. Film thickness: 35 nm <Film formation conditions for TaN film> Target: Ta target Sputtering gas: Mixed gas of Ar gas and N2 (volume ratio of N2 gas in the mixed gas (N2 / (Ar + N2)) = 0.17, gas pressure: 2.0×10 -1 Pa) Input power density per target area: 4.3 W / cm 2 Film formation rate: 0.029 nm / sec Film thickness: 60 nm Alternatively, an absorption layer containing RuB (RuB film) was formed on the protective film by magnetron sputtering. The film formation conditions for the absorption layer containing RuB (RuB film) are as follows. <Film formation conditions for RuB film> Target: Ru target B target Sputtering gas: Ar gas (gas pressure: 2.0×10 -1 Pa) Input power density per Ru target area: 0.2 W / cm 2 Input power density per B target area: 10.0 W / cm 2 Film formation rate: 0.013 nm / sec The composition ratio (at%) of RuB is Ru:B = 80:20. Film thickness: 35 nm

[0060] The following etching resistance evaluations (1) to (3) were performed on the EUV mask blank obtained by the above procedure. For the following evaluations (1) to (3), similar evaluation results can be obtained for those in which the absorption layer is not laminated on the protective film or those in which the Rh film is formed on the silicon wafer. The film composition in each example was analyzed using an X-ray Photoelectron Spectroscopy (manufactured by ULVAC-PHI, Inc.).

[0061] (1) Evaluation of dry etching resistance using a mixed gas of oxygen gas and chlorine gas as the oxygen-based gas A sample with a protective film (Rh film) formed was placed on the sample stage of an ICP (inductively coupled type) plasma etching apparatus, and ICP plasma etching was performed under the conditions shown below to obtain the etching rate. Also, a sample with an absorption layer containing RuON, RuN, or RuB (RuON film, RuN film, or RuB film) formed was placed, and the etching rate was obtained in the same procedure. ICP antenna bias: 200 W Substrate bias: 40 W Trigger pressure: 3.5×10 0 Pa Etching pressure: 3.0×10 -1 Pa Etching gas: O2 and Cl2 mixed gas Gas flow rate (Cl2 / O2): 10 / 10sccm The etching rate of the Rh protective film calculated by the above etching was 0.4 nm / min. The etching rates of the absorption layers containing RuON, RuN, and RuB (RuON film, RuN film, or RuB film) were 45.8 nm / min, 18.3 nm / min, and 12.3 nm / min, respectively. The etching selectivity of the Rh protective film to the absorption layers containing RuON, RuN, and RuB (RuON film, RuN film, or RuB film) was 8.7 × 10 -3 , 2.2×10 -2 , 3.3×10 -2 This is sufficiently slow compared to the etching rate of the absorption layer (RuON film, RuN film, or RuB film), and therefore has sufficient resistance to dry etching using a mixed gas of oxygen gas and chlorine gas as the oxygen-based gas.

[0062] The sample, in which the Si / Mo multilayer reflective film and the Rh film were formed on the substrate by the above procedure, was etched for 60 seconds under the same conditions as above. The composition of the sample surface before and after the etching process was analyzed using an X-ray photoelectron spectroscopy analyzer (XPS). The composition before the etching process was Rh:Si:Mo=81.4:17.3:1.3, and the composition of the sample after the etching process was Rh:Si:Mo=81.0:18.4:0.6. There was almost no difference in the composition of the sample before and after etching. Note that Si and Mo were detected because the resolution of XPS in the depth direction is about several nm to 10 nm, and the Si film and Mo film that are the base of the Rh film are detected. The sample after etching was observed using a transmission electron microscope (TEM), and the results are shown in Figure 5. The TEM image also confirmed that the Rh protective film was still present after etching.

[0063] (2) Evaluation of dry etching resistance using fluorine-based gas as the halogen-based gas (1) Similar to (1), ICP plasma etching was performed under the conditions shown below to determine the etching rate. Also, a sample with an absorption layer (TaN film) containing TaN was installed, and the etching rate was determined in the same procedure. ICP antenna bias: 100 W Substrate bias: 40 W Trigger pressure: 3.5×10 0 Pa Etching pressure: 3.0×10 -1 Pa Etching gas: Mixed gas of He and CF4 Gas flow rate (He / CF4): 12 / 12 sccm The etching rate of the Rh protective film calculated by the above etching was 1.4 nm / min. Also, the etching rate of the absorption layer (TaN film) containing TaN was 22.1 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer (TaN film) containing TaN was 0.063, which was sufficiently slow compared to the etching rate of the absorption layer (TaN film). Therefore, it has sufficient resistance to dry etching using fluorine-based gas as the halogen-based gas.

[0064] (3) Evaluation of SPM resistance A sample with a protective film (Rh film) formed was immersed in the following solution, and the change in film thickness before and after the treatment was investigated. Solution: Concentrated sulfuric acid: Hydrogen peroxide = 3:1 (volume ratio) Solution temperature: 100 °C Treatment time: 20 minutes After the immersion treatment, the film thickness of the Rh film increased by about 0.7 nm, and it was confirmed that the SPM resistance was not a problem.

[0065] <Example 2> Example 2 was carried out in the same procedure as Example 1, except that an Rh film (film thickness 2.5 nm) was formed as the protective film under the following conditions. <Film formation conditions of Rh film> Target: Rh target Sputtering gas: Mixed gas of Ar gas and N2 gas (volume ratio of N2 gas in the mixed gas (N2 / (Ar+N2)) = 0.31, gas pressure: 1.5×10 -1 Pa) Input power density per target area: 3.7 W / cm 2 Film deposition rate: 0.037 nm / sec Also, a protective film (Rh film) was deposited as a sample on a sample stage (4-inch quartz substrate) under the same conditions as above. For the above sample, the film density was measured using the X-ray reflectometry (XRR) method. The film density of the Rh film was 11.9 g·cm -3 It was. XRD measurement was performed on this sample. No sharp peak was observed in the obtained diffraction peak, and it was confirmed that the crystal state of the film was an amorphous structure or a microcrystalline structure. The etching rate of dry etching using a mixed gas of oxygen gas and chlorine gas as the oxygen-based gas was 0.77 nm / min, and the etching rate of dry etching using a fluorine-based gas as the halogen-based gas was 2.7 nm / min. The etching selectivity with respect to the absorption layer containing RuON and the etching selectivity with respect to the absorption layer containing TaN were 0.017 and 0.12, respectively, and both were sufficiently slower than the etching rate of the absorption layer. Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and chlorine gas as the oxygen-based gas and dry etching using a fluorine-based gas as the halogen-based gas.

[0066] <Example 3> Example 3 was carried out in the same procedure as Example 1 except that an RhRu film (film thickness 2.5 nm) was deposited as a protective film under the following conditions. <Film deposition conditions of RhRu film> Target: Rh target Ru target Sputtering gas: Ar gas (gas pressure: 2.0×10 -1 Pa) Input power density per Rh target area: 3.7 W / cm 2 Input power density per Ru target area: 1.5 W / cm 2 Film deposition rate: 0.58 nm / sec The composition ratio (at%) of RhRu is Rh:Ru = 75:25. As the oxygen-based gas, the etching rate of dry etching using a mixed gas of oxygen gas and chlorine gas was 1.0 nm / min. As the halogen-based gas, the etching rate of dry etching using a fluorine-based gas was 3.2 nm / min. The etching selectivity with respect to the absorption layer containing RuON (RuON film) and the etching selectivity with respect to the absorption layer containing TaN (TaN film) were 0.022 and 0.14, respectively, both being sufficiently slower than the etching rate of the absorption layer (RuON film, TaN film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and chlorine gas as the oxygen-based gas and dry etching using a fluorine-based gas as the halogen-based gas.

[0067] <Example 4> Example 4 was carried out in the same procedure as Example 1, except that an RhRu film (film thickness 2.5 nm) was formed as the protective film under the following conditions. <Film formation conditions of RhRu film> Target: Rh target Ru target Sputtering gas: Ar gas (gas pressure: 2.0×10 -1 Pa) Input power density per Rh target area: 3.7 W / cm 2 Input power density per Ru target area: 4.7 W / cm 2 Film deposition rate: 0.88 nm / sec The composition ratio (at%) of RhRu is Rh:Ru = 50:50. As the oxygen-based gas, the etching rate of dry etching using a mixed gas of oxygen gas and chlorine gas was 1.2 nm / min. As the halogen-based gas, the etching rate of dry etching using a fluorine-based gas was 3.7 nm / min. The etching selectivity with respect to the absorption layer containing RuON (RuON film) and the etching selectivity with respect to the absorption layer containing TaN (TaN film) were 0.026 and 0.17, respectively, and both were sufficiently slow with respect to the etching of the absorption layer (RuON film, TaN film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and chlorine gas as the oxygen-based gas and dry etching using a fluorine-based gas as the halogen-based gas.

[0068] <Example 5> Example 5 was carried out in the same procedure as Example 1 except that an RhO film (film thickness: 2.5 nm) was formed as the protective film under the following conditions. <Film formation conditions of RhO film> Target: Rh target Sputtering gas: Mixed gas of Ar gas and O2 (volume ratio of O2 gas in the mixed gas (O2 / (Ar + O2)) = 0.31, gas pressure: 1.5×10 -1 Pa) Input power density per Rh target area: 3.7 W / cm 2 Film formation rate: 0.073 nm / sec The composition ratio (at%) of RhO is Rh:O = 42:58. As the oxygen-based gas, the etching rate of dry etching using a mixed gas of oxygen gas and chlorine gas was 1.4 nm / min. As the halogen-based gas, the etching rate of dry etching using a fluorine-based gas was 5.0 nm / min. The etching selectivity with respect to the absorption layer containing RuON (RuON film) and the etching selectivity with respect to the absorption layer containing TaN (TaN film) were 0.030 and 0.22, respectively, and both were sufficiently slower than the etching rates of the absorption layers (RuON film, TaN film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and chlorine gas as the oxygen-based gas and dry etching using a fluorine-based gas as the halogen-based gas.

[0069] <Example 6> Example 6 was carried out in the same procedure as Example 1 except that an Ru film (film thickness: 2.5 nm) was formed as the protective film under the following conditions. <Film formation conditions of Ru film> Target: Ru target Sputtering gas: Ar gas (gas pressure: 2.0×10 -1 Pa) Input power density per Ru target area: 6.2 W / cm 2 Film formation rate: 0.053 nm / sec As the oxygen-based gas, the etching rate of dry etching using a mixed gas of oxygen gas and chlorine gas was 20.0 nm / min. The etching selectivity with respect to the absorption layer containing RuON (RuON film) was 0.44, which was not sufficient. Also, a sample in which an Si / Mo multilayer reflective film and an Rh film were formed on a substrate by the above procedure was etched for 60 seconds using an oxygen-based gas under the same conditions as in Example 1. For the samples before and after the etching treatment, the composition of the sample surface was analyzed using XPS. The composition before the etching treatment was Ru:Si:Mo = 89.3:9.9:1.0, and the composition after the etching treatment was Ru:Si:Mo = 3.8:92.9:3.3. After the etching treatment, the Ru film of the protective film disappeared, and damage to the multilayer reflective film was a concern. The reason why Si and Mo were detected is that since the depth resolution of XPS is about several nm to 10 nm, the Si film and Mo film underlying the Ru film were detected. Also, the results of TEM observation of the sample after the etching treatment are shown in Fig. 6. It was confirmed from the TEM image that the Ru protective film disappeared after the etching treatment.

[0070] <Example 7> Example 7 was carried out in the same procedure as in Example 1, except that an RhSi film (film thickness 2.5 nm) was formed as a protective film under the following conditions. <Film formation conditions of RhSi film> Target: Rh target Si target Sputtering gas: Ar gas (gas pressure: 2.0×10 -1 Pa) Input power density per Rh target area: 3.7 W / cm 2 Input power density per Si target area: 6.9 W / cm 2 Film formation rate: 0.083 nm / sec The composition ratio (at%) of RhSi is Rh:Si = 60:40. As the oxygen-based gas, the etching rate of dry etching using a mixed gas of oxygen gas and chlorine gas was 1.2 nm / min. As the halogen-based gas, the etching rate of dry etching using a fluorine-based gas was 7.6 nm / min. The etching selectivity with respect to the absorption layer containing TaN (TaN film) was 0.34, which was not sufficient. Therefore, there is a risk that the multilayer reflective film may be damaged during the etching of the absorption layer containing TaN (TaN film).

[0071] <Example 8> Example 8 was prepared in the same procedure as Example 1 to produce an EUV mask blank, except that an absorption layer containing RuTa (RuTa film) was formed as the absorption layer under the following conditions using magnetron sputtering, and the following etching resistance evaluation (4) was performed. For the following etching resistance evaluation (4), similar evaluation results can be obtained even when an Rh film or an absorption film is formed on a silicon wafer. The film composition in each example was analyzed using an X-ray Photoelectron Spectroscopy (manufactured by ULVAC-PHI, Inc.). <Film formation conditions of RuTa film> Target: Ru target Ta target Sputtering gas: Ar gas (gas pressure: 1.5×10 -1 Pa) Input power density per target area: Ru: 7.5 W / cm 2 Ta: 1.2 W / cm 2 The composition ratio (at%) of RuTa is Ru:Ta = 82:18. Film formation rate: 0.16 nm / sec Film thickness: 35 nm

[0072] (4) Evaluation of dry etching resistance using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas Similar to the etching resistance evaluation (1), ICP plasma etching was performed under the conditions shown below to determine the etching rate. Also, a sample with an absorption layer containing RuTa (RuTa film) was placed, and the etching rate was determined in the same procedure. ICP antenna bias: 200 W Substrate bias: 40 W Trigger pressure: 3.5×10 0 Pa Etching pressure: 3.0×10 -1 Pa Etching gas: Mixed gas of O2 and CF4 When the gas flow rate (O2 / CF4) was 4 / 28 sccm, the etching rate of the Rh protective film calculated by the above etching was 1.0 nm / min. Also, the etching rate of the absorption layer containing RuTa (RuTa film) was 31.4 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer containing RuTa (RuTa film) was 3.3×10 -2 which is sufficiently slow compared to the etching rate of the absorption layer (RuTa film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas.

[0073] <Example 9> Example 9 was carried out in the same procedure as Example 8, except that an absorption layer containing RuTa (RuTa film) was formed as the absorption layer under the following conditions. <Film formation conditions of RuTa film> Target: Ru target Ta target Sputtering gas: Ar gas (gas pressure: 1.5×10 -1 Pa) Input power density per target area: Ru: 7.5 W / cm 2 Ta: 2.7 W / cm 2 The composition ratio (at%) of RuTa is Ru:Ta = 67:33. Film formation rate: 0.19 nm / sec Film thickness: 35 nm When the gas flow rate (O2 / CF4) was 4 / 28 sccm, the etching rate of the Rh protective film calculated by the above etching was 1.0 nm / min. Also, the etching rate of the absorption layer containing RuTa (RuTa film) was 14.0 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer containing RuTa (RuTa film) was 7.4×10 -2 and was sufficiently slow compared to the etching rate of the absorption layer. Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas.

[0074] <Example 10> Example 10 was carried out in the same procedure as Example 8, except that an absorption layer containing RuTa (RuTa film) was formed as the absorption layer under the following conditions. <Film formation conditions of RuTa film> Target: Ru target Ta target Sputtering gas: Ar gas (gas pressure: 1.5×10 -1 Pa) Input power density per target area: Ru: 7.5 W / cm 2 Ta: 4.7 W / cm 2 The composition ratio (at%) of RuTa is Ru:Ta = 54:46. Film formation rate: 0.22 nm / sec Film thickness: 35 nm When the gas flow rate (O2 / CF4) was 8 / 24 sccm, the etching rate of the Rh protective film calculated by the above etching was 1.3 nm / min. Also, the etching rate of the absorption layer containing RuTa (RuTa film) was 27.0 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer containing RuTa (RuTa film) was 4.8×10 -2 and was sufficiently slow compared to the etching rate of the absorption layer (RuTa film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas.

[0075] <Example 11> Example 11 was carried out in the same procedure as Example 8, except that an absorption layer containing RuTa (RuTa film) was formed as the absorption layer under the following conditions. <Film formation conditions of RuTa film> Target: Ru target Ta target Sputtering gas: Ar gas (gas pressure: 1.5×10 -1 Pa) Input power density per target area: Ru: 7.0 W / cm 2 Ta: 9.9 W / cm 2 The composition ratio (at%) of RuTa is Ru:Ta = 37:63. Film formation rate: 0.31 nm / sec Film thickness: 35 nm When the gas flow rate (O2 / CF4) was 8 / 24 sccm, the etching rate of the Rh protective film calculated by the above etching was 1.4 nm / min. Also, the etching rate of the absorption layer containing RuTa (RuTa film) was 15.7 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer containing RuTa (RuTa film) was 8.7×10 -2 and was sufficiently slow compared to the etching rate of the absorption layer (RuTa film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas.

[0076] <Example 12> Example 12 was carried out in the same procedure as Example 8, except that an absorption layer containing RuW (RuW film) was formed as the absorption layer by the magnetron sputtering method using the reactive sputtering method under the following conditions. <Film formation conditions of RuW film> Target: Ru target W target Sputtering gas: Ar gas (gas pressure: 1.5×10 -1 Pa) Input power density per target area: Ru: 7.5 W / cm 2 W: 0.9 W / cm 2 The composition ratio (at%) of RuW is Ru:W = 80:20. Film deposition rate: 0.16 nm / sec Film thickness: 35 nm When the gas flow rate (O2 / CF4) was 4 / 28 sccm, the etching rate of the Rh protective film calculated by the above etching was 1.1 nm / min. Also, the etching rate of the absorption layer containing RuW (RuW film) was 34.7 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer containing RuW (RuW film) was 3.3×10 -2 and was sufficiently slow compared to the etching rate of the absorption layer (RuW film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas.

[0077] <Example 13> Example 13 was carried out in the same procedure as Example 12, except that an absorption layer containing RuW (RuW film) was formed as the absorption layer under the following conditions. <Film formation conditions of RuW film> Target: Ru target W target Sputtering gas: Ar gas (gas pressure: 1.5×10 -1 Pa) Input power density per target area: Ru: 7.5 W / cm 2 W: 2.0 W / cm 2 The composition ratio (at%) of RuW is Ru:W = 66:34. Film deposition rate: 0.18 nm / sec Film thickness: 35 nm When the gas flow rate (O2 / CF4) was 4 / 28 sccm, the etching rate of the Rh protective film calculated by the above etching was 1.1 nm / min. Also, the etching rate of the absorption layer containing RuW (RuW film) was 26.3 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer containing RuW (RuW film) was 4.3×10 -2 and was sufficiently slow compared to the etching rate of the absorption layer (RuW film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas.

[0078] <Example 14> Example 14 was carried out in the same procedure as Example 12, except that an absorption layer containing RuW (RuW film) was formed as the absorption layer under the following conditions. <Film formation conditions of RuW film> Target: Ru target W target Sputtering gas: Ar gas (gas pressure: 1.5×10 -1 Pa) Input power density per target area: Ru: 7.5 W / cm 2 W: 3.5 W / cm 2 The composition ratio (at%) of RuW is Ru:W = 53:47. Film formation rate: 0.21 nm / sec Film thickness: 35 nm When the gas flow rate (O2 / CF4) was 8 / 24 sccm, the etching rate of the Rh protective film calculated by the above etching was 1.4 nm / min. Also, the etching rate of the absorption layer containing RuW (RuW film) was 23.6 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer containing RuW (RuW film) was 5.9×10 -2 and was sufficiently slow compared to the etching rate of the absorption layer (RuW film). Therefore, the Rh protective film has a sufficient etching selectivity with respect to the RuW absorption film. Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas.

[0079] <Example 15> Example 15 was carried out in the same procedure as Example 12, except that an absorption layer containing RuW (RuW film) was formed as the absorption layer under the following conditions. <Film formation conditions of RuW film> Target: Ru target W target Sputtering gas: Ar gas (gas pressure: 1.5×10 -1 Pa) Input power density per target area: Ru: 7.5 W / cm 2 W: 8.0 W / cm 2 The composition ratio (at%) of RuW is Ru:W = 30:70. Film formation rate: 0.31 nm / sec Film thickness: 35 nm When the gas flow rate (O2 / CF4) was 8 / 24 sccm, the etching rate of the Rh protective film calculated by the above etching was 1.4 nm / min. Also, the etching rate of the absorption layer containing RuW (RuW film) was 25.6 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer containing RuW (RuW film) was 5.5×10 -2 which was sufficiently slow compared to the etching rate of the absorption layer (RuW film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas.

[0080] <Example 16> Example 16 was carried out in the same procedure as Example 8, except that an absorption layer containing RuCr (RuCr film) was formed as the absorption layer by the magnetron sputtering method using the reactive sputtering method under the following conditions. <Film formation conditions of RuCr film> Target: Ru target Cr target Sputtering gas: Ar gas (gas pressure: 1.5×10 -1 Pa) Input power density per target area: Ru: 7.5 W / cm 2 Cr: 0.94 W / cm 2 The composition ratio (at%) of RuCr is Ru:Cr = 94:6. Film formation rate: 0.16 nm / sec Film thickness: 35 nm When the gas flow rate (O2 / CF4) was 4 / 28 sccm, the etching rate of the Rh protective film calculated by the above etching was 1.1 nm / min. Also, the etching rate of the absorption layer containing RuCr (RuCr film) was 19.1 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer containing RuCr (RuCr film) was 5.8×10 -2 and was sufficiently slow with respect to the etching rate of the absorption layer (RuCr film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas.

[0081] <Example 17> Example 17 was carried out in the same procedure as Example 16, except that an absorption layer containing RuCr (RuCr film) was formed as the absorption layer under the following conditions. <Film formation conditions of RuCr film> Target: Ru target Cr target Sputtering gas: Ar gas (gas pressure: 1.5×10 -1 Pa) Input power density per target area: Ru: 7.5 W / cm 2 Cr: 2.1 W / cm 2 The composition ratio (at%) of RuCr is Ru:Cr = 86:14. Film formation rate: 0.18 nm / sec Film thickness: 35 nm When the gas flow rate (O2 / CF4) was 4 / 28 sccm, the etching rate of the Rh protective film calculated by the above etching was 1.1 nm / min. Also, the etching rate of the absorption layer containing RuCr (RuCr film) was 26.5 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer containing RuCr (RuCr film) was 4.2×10 -2 and was sufficiently slow compared to the etching rate of the absorption layer (RuCr film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas.

[0082] <Example 18> Example 18 was carried out in the same procedure as Example 16, except that an absorption layer containing RuCr (RuCr film) was formed as the absorption layer under the following conditions. <Film formation conditions of RuCr film> Target: Ru target Cr target Sputtering gas: Ar gas (gas pressure: 1.5×10 -1 Pa) Input power density per target area: Ru: 7.5 W / cm 2 Cr: 3.5 W / cm 2 The composition ratio (at%) of RuCr is Ru:Cr = 77:23. Film formation rate: 0.21 nm / sec Film thickness: 35 nm When the gas flow rate (O2 / CF4) was 4 / 28 sccm, the etching rate of the Rh protective film calculated by the above etching was 1.1 nm / min. Also, the etching rate of the absorption layer containing RuCr (RuCr film) was 36.7 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer containing RuCr (RuCr film) was 3.0×10 -2 and was sufficiently slow compared to the etching rate of the absorption layer (RuCr film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas.

[0083] <Example 19> Example 19 was carried out in the same procedure as Example 16, except that an absorption layer containing RuCr (RuCr film) was formed as the absorption layer under the following conditions. <Film formation conditions of RuCr film> Target: Ru target Cr target Sputtering gas: Ar gas (gas pressure: 1.5×10 -1 Pa) Input power density per target area: Ru: 7.5 W / cm 2 Cr: 8.1 W / cm 2 The composition ratio (at%) of RuCr is Ru:Cr = 59:41. Film formation rate: 0.29 nm / sec Film thickness: 35 nm When the gas flow rate (O2 / CF4) was 4 / 28 sccm, the etching rate of the Rh protective film calculated by the above etching was 1.1 nm / min. Also, the etching rate of the absorption layer containing RuCr was 35.8 nm / min. The etching selectivity of the Rh protective film with respect to the absorption layer containing RuCr (RuCr film) was 3.0×10 -2 and was sufficiently slow compared to the etching rate of the absorption layer (RuCr film). Therefore, it has sufficient resistance to dry etching using a mixed gas of oxygen gas and fluorine-based gas as the oxygen-based gas.

[0084] Although the present invention has been described in detail with reference to specific embodiments, it will be apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on Japanese Patent Application No. 2020-201198 filed on December 3, 2020 and Japanese Patent Application No. 2021-174692 filed on October 26, 2021, the contents of which are incorporated herein by reference.

Explanation of reference numerals

[0085] 1a, 1b, 1c: EUV mask blank 2: EUV mask 11: Substrate 12: Multilayer reflective film 13:Protective film 14: Absorption layer 15: Diffusion barrier layer 16: Etching mask film 140: Absorbing layer pattern

Claims

1. On the board, a multilayer reflective film that reflects EUV light; a protective film for the multilayer reflective film; a reflective mask blank for EUV lithography, comprising: the protective film is made of rhodium (Rh) or a rhodium-based material containing Rh and at least one element selected from the group consisting of nitrogen (N), oxygen (O), carbon (C), boron (B), ruthenium (Ru), niobium (Nb), molybdenum (Mo), tantalum (Ta), iridium (Ir), palladium (Pd), zirconium (Zr) and titanium (Ti); A reflective mask blank for EUV lithography comprising a diffusion barrier layer between the multilayer reflective film and the protective film, the diffusion barrier layer containing at least one element selected from Nb, Ru, Ta, silicon (Si), Zr, Ti and Mo.

2. 2. The reflective mask blank for EUV lithography according to claim 1, wherein the protective film contains Rh and at least one element selected from the group consisting of N, O, C and B.

3. 3. The reflective mask blank for EUV lithography according to claim 1, wherein the protective film has a film thickness of 1.0 nm or more and 10.0 nm or less.

4. 4. The reflective mask blank for EUV lithography according to claim 1, wherein the surface roughness (rms) of the protective film surface is 0.3 nm or less.

5. 5. The reflective mask blank for EUV lithography according to claim 1, wherein the diffusion barrier layer further contains at least one element selected from the group consisting of O, N, C and B.

6. 6. The reflective mask blank for EUV lithography according to any one of claims 1 to 5, wherein the absorber layer contains at least one element selected from Ru, Ta, chromium (Cr), Nb, platinum (Pt), Ir, rhenium (Re), tungsten (W), manganese (Mn), gold (Au), Si, aluminum (Al), and hafnium (Hf).

7. The reflective mask blank for EUV lithography according to claim 6 , wherein the absorbing layer further comprises at least one element selected from the group consisting of O, N, C and B.

8. 8. The reflective mask blank for EUV lithography according to claim 1, further comprising an etching mask film on the absorption layer, the etching mask film containing at least one element selected from the group consisting of Cr, Nb, Ti, Mo, Ta and Si.

9. 9. The reflective mask blank for EUV lithography according to claim 8, wherein the etching mask film further contains at least one element selected from the group consisting of O, N, C and B.

10. A reflective mask for EUV lithography, comprising the reflective mask blank for EUV lithography according to any one of claims 1 to 9, wherein a pattern is formed in the absorbing layer.

11. forming a multilayer reflective film on a substrate that reflects EUV light; forming a protective film on the multilayer reflective film; forming an absorption layer on the protective film that absorbs EUV light; the protective film is made of Rh or a rhodium-based material containing Rh and at least one element selected from the group consisting of N, O, C, B, Ru, Nb, Mo, Ta, Ir, Pd, Zr, and Ti; A method for producing a reflective mask blank for EUV lithography, comprising: a diffusion barrier layer between the multilayer reflective film and the protective film, the diffusion barrier layer containing at least one element selected from Nb, Ru, Ta, silicon (Si), Zr, Ti and Mo.

12. 12. A method for producing a reflective mask for EUV lithography, comprising patterning an absorbing layer in a reflective mask blank for EUV lithography produced by the method for producing a reflective mask blank for EUV lithography according to claim 11 to form a pattern.

Citation Information

Patent Citations

  • Optical element and manufacturing method thereof, and manufacturing method of lithographic apparatus and semiconductor device

    JP2005505930A

  • Optical element for extreme ultraviolet ray, and projection aligner using the same

    JP2006173446A

  • Optical element and projection exposing device using it

    JP2006173502A

  • Reflective mask for EUV lithography

    JP2013514651A

  • Substrate with multilayer reflection film, manufacturing method therefor, method for manufacturing reflection-type mask blank, method for manufacturing reflection-type mask, and method for manufacturing semiconductor device

    JP2014170931A

Cited By

  • Substrate with multilayer reflective film, reflective mask blank, reflective mask, and method for manufacturing a semiconductor device.

    JP7862325B2

  • Multilayer reflective film-equipped substrate, reflective mask blank, reflective mask, and method for producing semiconductor device

    JPWO2022138434A1